2018
DOI: 10.6007/ijarbss/v8-i12/5243
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Outsourcing and Performance of Commercial Banks in Kenya

Abstract: Marketing of banking product offerings is an emerging phenomenon that has potential effect on performance of commercial banks especially in the prevailing situation where globally, the banking sector is struggling to bounce bank to positive performance since the 2007-2008 global financial crunch. In Kenya, commercial banks are facing performance challenges as evidenced by recent assumption of cost rationalization measures such as staff lay-offs and closure of redundant branches; acquisition, liquidation and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Accordingly, the set of items for the distinct research variables were therefore found to be reliable for use in the final study. The benchmark alpha index of 0.7 has been adopted by past research for making decision on reliability of research instrument [33,24,12,15,28,34].…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the set of items for the distinct research variables were therefore found to be reliable for use in the final study. The benchmark alpha index of 0.7 has been adopted by past research for making decision on reliability of research instrument [33,24,12,15,28,34].…”
Section: Methodsmentioning
confidence: 99%